Aorta–Right Atrial Tunnel: Is Surgical Correction Mandatory?. Issue 13 (29th March 2016) - Lee, Sunki; Kim, Sun Won; Im, Sung Il; Yong, Hwan Seok; Choi, Cheol Ung; Lim, Hong Euy; Na, Jin Oh
Abstract : Supplemental Digital Content is available in the text.